Evolution of Perceptions about the Essence of Capital as a Scientific Category and a Factor of the Socio-Economic Development - TARASENKOА.; HRYNCHAK, N.; PARKHOMENKO, V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The article’s objective is to investigate the logic of evolution in the essence and forms of capital under the impact of the changing sources and factors of socio-economic development and social wealth. The visions of capital prevailing from the middle of the eighteenth till the middle of the nineteenth century are analyzed, to demonstrate that although the classical tradition did not deny the impact of out-of-economic factors on the economy as a whole and the human behavior in particular, the analysis focused on the purely economic factors of growth and distribution of the social wealth. The paradigm of the classical school was changed in the end of nineteenth century by the emerging institutional theory: factor theories of economic growth were replaced by substantiations of multidimensional sources of socio-economic development. The twentieth century was marked by the two achievements: (i) the understanding that the social wealth could not be confined to the material wealth; (ii) a new vision of a mix of factors behind the socio-economic development: natural, technical and technological, and institutional, with research focus gradually shifting from material factors to information and institutional ones. The following significant move in the vision of capital was the line drawn between the notions of “economic growth” and “economic development”: emphasis on economic growth as the fundament of development made the economic theory inapplicable in studies of broader development perspectives. A new phase in the economics started in 70s of the twentieth century, with rise of the neo-institutional theory assuming that the material welfare of a nation could not be gained by means of traditional production factors and capital accumulation without a highly developed institutional structure of the society. The philosophical and economic rediscovery of capital was made by the neo-classical school: by treating capital as a way of value utilization rather than a tangible form, it denied a criterion of capital commonly adopted in the political economy of earlier times, i. e. its alienability, together with the materialistic approach to interpretation of capital. The set of capital parameters was expanded by including in it skills and qualifications (human capital), social relations and networks (social capital), political and economic institutes (institutional capital), and, eventually, intellectual objects of intangible nature. It shows that the forms of capital were transforming from tangible (material) to human and intellectual (intangible) ones. This phase is marked by rise of the theory of human capital, reflecting the cardinal change in the role of the human factor and its impact on science and technology development, production processes and labor productivity. The notion of “social capital” was introduced in economics by abandoning out-dated visions of capital as a purely materialistic phenomenon associated with the material production processes and adopting to broader concept related with social development, with emphasis changing from links of humans and wealth to relations between humans in a broader humanistic sense.